An Evaluation of the Performance of Higher Educational Institutions using Data Envelopment Analysis: An Empirical Study on Algerian Higher Educational Institutions (Global Journal of Human-Social Science, 2017)
The aim of this research paper is to clarify to evaluate the performance of the Algerian institutions of higher education using data envelopment analysis method based on the concept of benchmarking Five indicators of inputs as well as outputs that reflect three dimensions of teaching learning and scientific research were used were used total number of students enrolled in graduation total number of students enrolled in post-graduation permanent professors graduated students and scientific publications The findings of data envelopment analysis pointed out that there is a significant variation in the performance of the Algerian institutions of higher education in favor of the academic years It was highlighted that inefficient internal processes or poor conditions surrounding these processes were the main causes of the weak performance
Keywords: data envelopment analysis method; efficiency; performance indicators; performance evaluation